Experiencing English: A Textbook Evaluation on the Cultural Loads - Yunita Dewi Wahyuni; Novalia Rizkanisa; Bukhari Daud; Iskandar Abdul Samad (Universitas Syiah Kuala, 2019)
This research aimed at investigating the cultural contents implied in an English textbook. A qualitative method was used in this research which analyzed this English textbook. The data source of this research was the English textbook for junior high school students entitled “Experiencing English”. The instrument used for collecting data was documentation in the form of textbook. The data were analyzed by using Byram (1994) framework to investigate the aspects of culture. In this research, the nine aspects that have to be included in the EFL textbook were analyzed. The result showed that stereotypes and national identity was more frequently used in “Experiencing English” textbook. This aspect represents the target culture stereotypes and national identity commonly focused on the British and American cultures. In the other words, “Experiencing English” textbooks frequently used target language culture. Notwithstanding this fact, the source/local culture values as drafted in the 2013 curriculum was still implied in the textbook as intended to enable the students to reflect their own culture in English.